2010
DOI: 10.1007/s10728-010-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Managing Health(-Care Systems) Using Information Health Technologies

Abstract: This study aims to compare and contrast how specific information health technologies (IHTs) have been debated, how they have proliferated, and what they have enabled in Germany’s and England’s healthcare systems. For this a discourse analysis was undertaken that specifically focussed on future-scenarios articulated in policy documents and strategy papers released by relevant actors from both healthcare systems. The study reveals that the way IHTs have been debated and how they have proliferated depends on coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Discourse is historically situated (Iedema, 2007, p. 931) and constructed in a particular context (Fairclough & Wodak, 1997, p. 277). Thus, the way IT in health are debated and adopted depends on country-specific regulatory structures, their respective values, actors' organized interests, the status of health professionals (Mathar, 2011) and other resources they can draw on, as well as user practices (as depicted in Figure 1). Actors can include organizations, groups and individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Discourse is historically situated (Iedema, 2007, p. 931) and constructed in a particular context (Fairclough & Wodak, 1997, p. 277). Thus, the way IT in health are debated and adopted depends on country-specific regulatory structures, their respective values, actors' organized interests, the status of health professionals (Mathar, 2011) and other resources they can draw on, as well as user practices (as depicted in Figure 1). Actors can include organizations, groups and individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The high decentralization of the health system in Germany outlined a scenario of greater difficulty in the implementation of health information technologies when compared with the English context 13 . Regarding the development of health information systems, considering the need for the health professionals to accept and adhere to their use, the study from Portugal showed that the participatory design with a holistic approach may be an effective strategy 26 …”
Section: Resultsmentioning
confidence: 99%
“…From the viewpoint of territorial inequalities and use in rural areas, Brazil sees similar results and discussions presented in other countries in Latin America and Africa. 16,23 Nevertheless, reflections on the consequences of the public-private relationship existing in the country are very similar to European models, 13 as these can represent a challenge to the coordination of care and the overcoming of individual interests in the integration of information and macro-management.…”
Section: Continuing Professional Developmentmentioning
confidence: 95%
“…The multi-stage process of analyzing the HCI activities, as well as the need for the consistent solution of a large number of tasks and handling large volumes of data of various natures, necessitates the use of special information technologies [7][8][9]. The development and use of relevant information and analytical support in the process of analyzing the HCI activities will make it possible to obtain timely and objective assessments of their activities, which, in turn, will become the basis for effective management decisions [10][11][12][13].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%